No time like the future : an optimist considers mortality - Fox, Michael J., 1961- (New York : Flatiron Books, 2020)
The actor shares personal stories and observations about illness and health, aging, the strength of family and friends, and how perceptions about time affect the consideration of mortality.
Diagnosed at age 29, Fox is engaged in Parkinson's advocacy work, raising global awareness of the disease and helping find a cure through The Michael J. Fox Foundation for Parkinson's Research, the world's leading non-profit funder of PD science. Here he shares personal stories and observations about illness and health, aging, the strength of family and friends, and how our perceptions about time affect the way we approach mortality. Running through the narrative is the drama of the medical madness Fox recently experienced: the Parkinson's disease he's had since 1991, and a spinal cord issue that necessitated immediate surgery. He describes how his challenge to learn how to walk again, only to suffer a devastating fall, nearly caused him to ditch his trademark optimism. --
Introduction: Fall guy -- Family man -- Dog years -- Act too -- High times -- Double bogey -- Loco motion -- Unsafe at any speed -- Exile on Pain Street -- What to expect from my back in the future -- Showing some spine -- Metaphysical therapy -- Walk this way -- A crowded house -- Breaking dad -- A wing and a proverb -- Homeland security -- Head games -- Maryland, my Maryland -- The only thing to fear -- Father time -- All things considered -- Shake it off -- Midnight in the garden -- Epilogue.
Keywords: Fox, Michael J., -- 1961-; Fox, Michael J., -- 1961-; Actors -- Canada -- Biography; Actors -- United States -- Biography; Parkinson's disease -- Patients -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Rich & Famous; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY / People with Disabilities; Actors; Parkinson's disease -- Patients; Actors -- United States -- Biography; Actors -- Biography; Parkinsonism -- Biography; Canada; United States; Autobiographies; Autobiographies; Biographies; Autobiographies